Aplikasi Formulasi Bahan Pembenah Tanah terhadap Beberapa Sifat Kimia Tanah Berpasir dan Produksi Tanaman Padi - Aprilia, Intan Bella; Sasongko, Purnomo Edi; Siswanto, Siswanto (JURNAL AGROTROPIKA, 2024)
Sandy soil is part of the soil fraction with low nutrient content, organic matter, and cation exchange capacity. This is due to the leaching process so that nutrients are easily lost. The research aimed to improve the chemical characteristics of sandy soil and rice crop production due to the application of humic acid and silica. This research used of Completely Randomized Design method using soil amendment materials, namely humic acid (A) at the of 60 kg/ha and silica (S) at the of 5 tons/ha consisting of 6 combinations of comparisons repeated 4 times. Variables of analysis parameters include pH, cation exchange capacity, organic matter, N-NH4+, N-NO3- and rice crop production. The data obtained were analyzed by analysis  of variance (ANOVA). If the results showed a significant effect, it was continued with the Honestly Significant Difference (HSD) test at the 5% level. The results showed that the application of soil amendment in the from humic acid and silica with various treatments on sandy soil was only able to improve CEC by 3,18% and Organic-C by 0,08%. In contrast soil pH and N-available didn`t give significant results in improving soil chemical properties and rice crop production. It`s recommended to conduct further research on the dose used in soil amendments so that it can effect nitrogen parameters and rice crop production in sandy soil.  Keywords: humic acid, silica, sandy soil